If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(5 + -1x) + 2(3x + -4) = 2 8x + (5 * -1 + -1x * -1) + 2(3x + -4) = 2 8x + (-5 + 1x) + 2(3x + -4) = 2 Reorder the terms: 8x + -5 + 1x + 2(-4 + 3x) = 2 8x + -5 + 1x + (-4 * 2 + 3x * 2) = 2 8x + -5 + 1x + (-8 + 6x) = 2 Reorder the terms: -5 + -8 + 8x + 1x + 6x = 2 Combine like terms: -5 + -8 = -13 -13 + 8x + 1x + 6x = 2 Combine like terms: 8x + 1x = 9x -13 + 9x + 6x = 2 Combine like terms: 9x + 6x = 15x -13 + 15x = 2 Solving -13 + 15x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 15x = 2 + 13 Combine like terms: -13 + 13 = 0 0 + 15x = 2 + 13 15x = 2 + 13 Combine like terms: 2 + 13 = 15 15x = 15 Divide each side by '15'. x = 1 Simplifying x = 1
| 3x^2=-18 | | 3r-4=5(r-1) | | 3k=45 | | 2(7/2)+y=11 | | 3(x-2)=-31+4x | | 8m+m-m-3m+2m=14 | | 3(2x+5)-5= | | 19s-13s-6s+s=19 | | 8.8=m-14.4 | | 7x+2y=94 | | 152+8x=-82-10x | | v^2-5vy-14y^2=0 | | 5r-1=-3(-4+3r)+r | | 2y=7x-94 | | (2s-9)(8s+1)=0 | | 19s-13s-6s=19 | | 3c+2=6c | | 5(m+9)=40+2m+5+3m | | 10x^2=60x+2 | | 4+2(x-8)=8-4x+2 | | -(6x-2y-2)= | | 42s+s^2-s^3=0 | | 6x+9=9x-6 | | 84=12n | | (6t-7)(t+6)=0 | | log(2t+4)=log(13-3t) | | 20+b-b^2=0 | | 11x+4.4=8 | | (6x+1)(x+2)=0 | | x=4(x-1)+1 | | y=2cos(x^2) | | 6x+28=2x+52 |